On a half-forgotten but very powerful method for coherent spectroscopy of molecules. (March 2019) - Makarov, A A; Ryabov, E A
Abstract: The sum-frequency generation involving two infrared laser quanta and a single visible-range laser quantum is a four-wave mixing process that is virtually not used in practice. Nevertheless, this process provides an extremely high selectivity with respect to the Q-branch of the two-photon vibrational transition in molecules. We explore here two publications: one that is more than thirty years old, and another that appeared in 2018, to show broad potential applications of the method. The objective reasons why this potential has not been used so far are discussed.